In Vitro Acid Resistance of Pathogenic Candida Species in Simulated Gastric Fluid - Eri Ikeda; Masaya Yamaguchi; Masayuki Ono; Shigetada Kawabata (Gastro Hep Advances)
Background and Aims: Although species in the fungal genus Candida are often commensal residents of the gastrointestinal (GI) tract, they can also cause high-mortality systemic candidiasis. Most pathogenic Candida species are dimorphic fungi that exist predominantly in filamentous forms in the invading tissues. Candida albicans is the most prominent pathogen among Candida species, but nonalbicans Candida species have also emerged as important pathogens. The stomach is the most acidic niche in the GI tract and is maintained at pH 1–2 in healthy individuals. The aim of the present study was to determine whether Candida species can survive in gastric fluid and to observe their morphology under varied pH conditions. Methods: We investigated the in vitro survival of the pathogenic Candida species C. albicans, Candida glabrata, Candida parapsilosis, and Candida tropicalis in simulated gastric fluid. Results: We first described that a portion of the 4 Candida species can survive under highly acidic conditions. Moreover, dimorphic Candida species, namely, C. albicans, C. parapsilosis, and C. tropicalis, exhibited yeast–hyphal transition in simulated gastric fluid with elevated pH. Pathogenic filamentous cells had lower acid resistance than yeast cells. Conclusion: These findings may illuminate the migration to the lower GI tract by commensal fungi of the oral cavity.